Law Enforcement by Police against Children Who Committed Criminal Acts of Violence that Caused Death - Roby Muhtar; Siti Rodhiyah Dwi Istinah (Law Development Journal, 2021)
The purpose of this research; to know and analyze law enforcement by the police against children who commit violent crimes that lead to death. To find out and analyze the obstacles experienced by the police, especially the Criminal Investigation Unit (Criminal Investigation) against children who commit a criminal act that causes death and the solution.The method used by researchers isjuridical sociological approach to law and The specifications in this research are descriptive. Based on the results of the study it was concluded that in investigating cases of criminal acts with violence committed by underage school students, they are guided by KUHAP, KUHP. There are still investigators who are only guided by the disposition of the leadership in handling criminal acts against perpetrators of underage school students showing a low level of professionalism of investigators, so there are frequent violations of the provisions of the Criminal Procedure Code. Obstacles experienced by the police, especially the Criminal Investigation Unit (Criminal Investigation) against a child who commits a crime that causes death, which is usually found when the family does not cooperate and tries to cover up the existence of their child as the perpetrator of the crime. Efforts to overcome the obstacles faced by the police, especially the Criminal Investigation Unit, are: Outreach in schools and in the community. Patrol in certain areas is one of the police activities by 2 (two) or more members of the National Police.